The quality of life, neck and shoulder area dysfunction and upper body posture among people with and without moderate myopia - HANNA KALAJAS-TILGA; KULDAR KALJURAND; DORIS VAHTRIK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: The current study aimed to examine the quality of life, dysfunction in the neck area and upper body posture among people with moderate myopia and to analyse the relationship between myopia and upper body posture. Material and methods: ‪Participants were 11 people with moderate myopia (MG) and 11 people without myopia (CG). The general quality of life was evaluated with the 36-Item Short Form Health Survey (SF-36), neck area pain with the Visual Analogue Scale (VAS) and discomfort with the Neck Bournemouth Questionnaire (NBQ). The National Eye Institute Visual Functioning Questionnaire (NEI-VFQ25) was used to measure vision-targeted health. Upper body was evaluated with the New York Posture Rating Chart. Correlation analysis examined the relationship between head position and vision. Results: ‪The general quality of life and upper body posture characteristics did not differ significantly in MG as compared to CG. A significant difference in NBQ (p < 0.05), NEI-VFQ25 (p < 0.05) and VAS (p < 0.01) was established between MG and CG. A significant relationship (r=-.691) between increasing severity of myopia and head position was found. Conclusions: The study findings highlight the complaints of people with moderate myopia compared to people without myopia concerning both their quality of life and musculoskeletal problems.